Atheroma-like sclerotic material causing obstruction of a central venous catheter: A case report - Naoya Sakamoto; Kouji Masumoto; Tomohiro Aoyama; Noriaki Sakamoto (Elsevier, 2023)
Introduction: The long-term management of central venous catheters (CVCs) is extremely important in various pediatric treatments. However, in addition to catheter infections, catheter lumen obstruction (CLO) often causes treatment to be interrupted.Thrombosis is a well-known cause of CLO. However, we experienced a case of occlusion not caused by a thrombus but by an atheroma-like sclerotic substance. Case presentation: The patient was an 18-month-old girl born with extremely low weight (23 weeks' gestation, birth weight 497 g). She had multiple surgeries for ileal perforation and postoperative adhesive bowel obstruction, resulting in short bowel syndrome. Owing to that condition, she was managed with parenteral nutrition administered via a central venous catheter. The content of the parenteral nutrition included amino acid preparations, sugar, heparin, and fat emulsion. During the catheter replacement procedure when she was aged 18 months, yellow embolic material was recognized with blood film in the lumen of the catheter. The embolic material was thought to be the atheroma-like sclerotic substance shown on the pathologic findings.After the replacement of the catheter, the patient is still under central venous nutritional management and is being monitored to see if a similar obstruction occurs. Conclusion: In the case of CLO, we cannot detect the cause by any kind of examination. Therefore, we must pay special attention to the method of recanalization to prevent not only spillage of microbes and blood clotting, but also severe embolism due to a sclerotic substance.